Endoscopic Endonasal Pituitary Surgery: Impact of Surgical Education on Operation Length and Patient Morbidity - Dedhia, Raj C.; Lord, Christopher A.; Pinheiro-Neto, Carlos D.; Fernandez-Miranda, Juan C.; Wang, Eric W.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Objectives To determine the difference in operative times and associated complications for cases performed solely by attending-level surgeons versus cases assisted by surgeons-in-training for endoscopic endonasal pituitary surgeries.Design Retrospective chart review.Setting Tertiary-care academic medical center.Participants A total of 228 patients having undergone endoscopic endonasal pituitary surgery from 2005 to 2011.Main Outcome Measure Duration of surgery comparing attending only (AO) and trainee-assisted (TA) surgeries.Results Thirty-seven (19%) of 198 cases were identified as AO surgeries, the remaining 161 (81%) were TA. Operative times (minutes) for the AO group were significantly shorter than the TA group (149.1 ± 54.8 vs 219.5 ± 83.7, p < 0.001). The AO group had fewer intraoperative cerebrospinal fluid leaks (30% vs 39%, p = 0.318), decreased estimated blood loss (408 mL vs 523 mL, p = 0.176), fewer postoperative complications (27% vs 37%, p = 0.268), and shorter length of stay (3.5 vs 4.3 days, p = 0.294).Conclusions This is the first study in otolaryngology or neurosurgery to compare operative times and outcomes for AO versus TA cases at a single academic institution. Operative times were significantly decreased and a trend toward a decrease in patient morbidity was noted for cases performed solely by attendings. The valuation of teaching activities in the operating room is a necessary first step toward optimizing the allocation of resources and funding of surgical education.
Keywords: skull base surgery; pituitary surgery; residency training; surgical education; endoscopic endonasal approach